Pengaruh Penggunaan Examples Non Examples Terhadap Hasil Belajar Siswa Kelas IV SDN Dahian Tunggal Tahun Ajaran 2021/2022 - Anuriah Anuriah; Roso Sugiyanto; Ichyatul Afrom Afrom; Sapriline Sapriline (FKIP Universitas Palangka Raya, 2022)
This research is motivated by the thematic learning outcomes of students in grade IV SDN Dahian Tunggal, most of whom have not reached the KKM, there are still students who find it difficult to understand thematic material. Many students are still less active in participating in learning activities, there is less variety of learning models that teachers apply so that student learning outcomes are less than optimal. The purpose of this study was to determine the effect of the use of examples non examples learning model on student learning outcomes. The type of research used is True Experimental Design using a pre-test post-test control group design model. This research was conducted in class IV-A as an experimental class with a total of 28 students and IV-B as a control class with a total of 22 students. From the results of the data analysis, it was obtained that tcount was 2,509 and ttable was 1,677 with a significant level of 5% and dk (n1+n2-2). This shows that there is an influence of the learning model on the learning outcomes of the